Implementing Smart Governance in Realizing a Smart City: Case Study Catur Tourism Village, Bangli, Indonesia - I Gede Bayu Adi Prabawa; Kuncoro Galih Pambayun; Sampara Lukman (Institut Pemerintahan Dalam Negeri, 2025)
The implementation of Smart Governance in villages across Bangli Regency serves as a foundation for the realization of Bangli Smart City. One of the pilot villages for this initiative is Desa Wisata Catur (Catur Tourism Village). However, its implementation still faces several challenges, such as suboptimal intersectoral collaboration and limited human resources in the village. This study aims to examine how smart governance is implemented in Catur Tourism Village, Kintamani District, Bangli Regency. The research adopts a qualitative descriptive method with an inductive approach, as outlined by Sugiyono. Data were collected through interviews, observations, and documentation, and analyzed using data reduction, information presentation, and conclusion drawing techniques. The findings indicate that in the public and social services dimension, public services in Catur Village have been successfully developed through multi-stakeholder collaboration, particularly by promoting Subak Abian as a tourism asset based on traditional values and social inclusiveness. in the participation in decision-making dimension, community participation is institutionalized through customary forums and formal institutions, resulting in inclusive, transparent, and accountable village policies. In the provision of facilities and infrastructure dimension, the development of tourism and agricultural infrastructure has supported community productivity while preserving local cultural values. Lastly, in the online services dimension, digital services remain limited to a basic informational website due to constraints in human resources and funding. This study concludes that the implementation of smart governance in Catur Tourism Village has been progressing well, with local cultural values playing a central role in its realization. Nevertheless, the village still faces limitations in optimizing online services to fully leverage digitalization in rural governance.